Characterization Microencapsul Pepton from Spoiled By Catch Fish Using Spray Drying Methods - Barokah, Giri Rohmad; Ibrahim, Bustami; Nurhayati, Tati (Jurnal Pengolahan Hasil Perikanan Indonesia, 2017)
Spoiled by catch fish is one of catch produce that have low economic value. Utilization and how to increase the selling value of byproducts by making peptone. Peptone fish is a derivative product or derivative of a water-soluble protein hydrolyzate and does not undergo any coagulation process in hot water. This research aim is to produce peptone with spoiled by catch fish as raw materials using microencapsulation technique and maltodextrin as coating ingredients. Microencapsulate of peptone has a chemical composition with moisture content 8.95%, ash content 5.26%, protein content 62.79%, Fat content 0.44% and carbohydrate content 21.48%. The chemical characteristic peptone by-catch rotten fish indicate that product has solubility 98.87%, nitrogen total 10.05%, α amino nitrogen 1.22%, AN/TN 12.14%, salt content 8.04% and pH  6.69. Microencapsulate peptone has a physical characteristic with lightness value 60.01, whiteness value 57.44 and dominated red color value 1.70 and yellow color value 10.33. The water activity of microencapsulating spoiled by catch fish peptone at room temperature of storage after 5 hours was lower than peptone spoiled by catch fish without micro encapsulation and product of commercial peptone. Amino acid analysis results indicate that microencapsulate spoiled by catch fish peptone arginine, serine, tyrosine,histidine and threonine amino acids higher than peptone spoiled by catch fish without microencapsulation and commercial product of peptone. Microorganism growth curve with Optical Density (OD). That indicatesmicroencapsulate spoiled by catch fish peptone has bacterial growth curve more good than a commercial product of peptone and peptone spoiled by catch fish without micro encapsulation.